Post-traumatic fat embolism syndrome: a case report - Abel Arroyo-Sánchez; Rosa Aguirre-Mejía (Horizonte Médico, 2018)
Post-traumatic fat embolism syndrome (FES) is a potentially lethal and poorly suspected complication. We present a case of FES diagnosed clinically and confirmed by current diagnostic criteria. The epidemiological characteristics, risk factors, clinical features and favorable evolution after treatment were as reported. We review the literature and propose measures to reduce the risk of its presentation and improve early diagnosis.